Critique of the sense in W. V. O. Quine's philosophy - Hlushchenko, E. Vyacheslavovych (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article is devoted to the studies the problems of interpretations and representations of the concept of “sense” in logical semantics , which has been analyzed by the outstanding American philosopher and mathematician of the middle and a second half of the XX century – Willard Van Orman Quine, who has snooped far enough into the presented problem in numerous of his works, mainly, his “Word and Object” and “From a Logical Point of View”. The central critical theories of understanding Quine’s thought of the sense is seen at another angle, that is, as a main concept that gets some responds of the philosophers in post-analytical philosophy tradition, along with it is reviewed as a broadly interpreted concept. Additionally, modes of such critique can be found as in some classic works of the philosophers like D. Davidson or M. Dummett, or as of such modern analytical philosophers as: M. Baghramian, L. Komacha, P. Livingston, J. Smith, and others. About this material few modern works and Quine's as well have been particularly researched, and of our opinion, the movement of such explanation of the sense problem in Quine's works keeps coming to be emphasized in today's philosophy. We result this work on that the critique of the sense in Quine's works hadn't been done the way perfectly: not enough enlightened though. Hereby we claim to keep monitoring and not to stop studying of the metaphysical context of works and cultural as well. The better that point becomes to get larger area to study the more successful the research is expected. That way of criticizing half-metaphysical concepts aimed as a method, on the one hand, is required for a more advanced investigations of the proliferation in post-analytical philosophy works, and, on the other hand, as a reason of ideas and views separation, which are not relevant to the traditional analytic philosophy, is taken and viewed using examples. New critique of few aspects of Quine's philosophy are necessary to get closer to the as the philosopher's ideas to the newest ideas for the development of the science as well. Many key and well points can be gotten from the way to analyze the works. Interpretations of meaning of the concept of sense in the different papers of analytical philosophers is supposed to change the key direction of the considered this topic.

Стаття присвячена дослідженню проблеми інтерпретації та репрезентації концепту логічної семантики «смислу», яка розглядалася видатним американським філософом та математиком середини і другої половини ХХ століття – Вілардом Ван Орманом Квайном, багато праць якого занурені вглиб поданої проблематики, перважно, його «Слово та об’єкт» та «З логічної точки зору». Найголовніша критична теорія розуміння думок Квайна щодо смислу розглянута під таким кутом, який набуває відгуків у філософів як в аналітичнй, так і пост-аналітичній традиції філософії. Разом із цим розглядається як доволі широко інтерпретований концет. Також, типи такої критики можуть бути знайдені серед праць таких класиків аналітичної філософії, як Д. Девідсон та М. Дамміт, але і в сучасних послідовниках цього напряму, зокрема: М. Багхраміан, Л. Комахи, П. Лівінґстона, Д. Сміта та інших. Щодо цього матеріалу кілька сучасних праць, разом з працями Квайна, частково є розглянутими, тоді ж як, на нашу думку ця спадщина трактування продовжує підкреслювати значущість цієї проблеми до сьогодні. Результатами нашої роботи є зауваження щодо прогалин в питанні дослідження концепту «смислу» в філософії Квайна. Цим ми наполягаємо на подальшому догляду як інтерпретації метафізичної площини контексту його робіт, так і культурологічної. Чим більше ці ділянки для дослідження набувають, тим більш успішним воно очікується. Метод критики напів метафізичних концептів потрібен задля більш досконалого дослідження проліферації ідей концепції смислу в пост-аналітичній філософії, і, як чинник відмінності від традиційної аналічної філософії, що послуговується прикладом змін. Нова критика деяких аспектів філософії Квайна, таким чином, змушна наближатися до розвитку науки в цілому. Чимало ключових та важливих деталей може бути взято з аналізу його праць. Інтерпретації значення концепту смислу в різних працях аналітичних філософів можливо розглядати як серйозний чинник впливу щодо напрямку змін в самій аналітичній традиції.
Критика сенсу у філософії В. В. О. Кайна
Keywords: naturalistic epistemology; sense; formal semantics; analytical philosophy; натуралістична епістемологія; смисл; формальна семантика; аналітична філософія